THE EFFECT OF WORK ENVIRONMENT, JOB SATISFACTION AND WORK MOTIVATION ON WORKER PERFORMANCE - Al Qohirie, Mohammad Irfan; Puspitasari, Ekas Mibari; Siregar, Fitri Anggraini (Universitas Dharmawangsa, 2025)
The results of previous relevant research include important types of research for a study of literature review. The previous research is very relevant and functions in complementing theories and phenomena on the relationship or influence between variables. This article contains a review related to the influence of the work environment, job satisfaction and work motivation on worker performance. The writing of this article is based on the aim of building a hypothesis of the influence of two variables so that it can be used as a guideline in research that will be carried out further. The research method used in this study is the literature review method or literature study and the data obtained comes from literature sources that are in accordance with the topic discussed, then analyzed based on the data that has been obtained, collected and discussed to then draw conclusions. The results and implications of this study are the influence of the work environment, job satisfaction and work motivation on worker performance.